Floco-sedimentação seguida de processos de separação por membranas para tratamento de efluentes de lagos de estabilização visando o reúso - Fabro, Lucas Fernando (2017)
To adapt to the new paradigms that present themselves is a challenge for the urban centers, since they continue to grow, they need to be structured and seek alternatives to meet the demands of water consumption that minimize damages to the environment and allow the renewal of their resources. In this context, treated sewage plays a key role and can be a substitute for water supply for a number of non-potable purposes, and if proven for priority uses, contributing to the planning and sustainable management of water resources. The effluent generated by conventional sewage treatment processes in STS (stabilization ponds), generally meets the launching standards recommended in legislation, however, contain numerous pollutants that need to be removed in order to achieve sufficient quality for reuse. Therefore, it is necessary to use post-treatments with a view to improving the quality of this effluent, allowing the practice of reuse, and integrated treatment systems (hybrids) have been considered viable alternatives from a technical-economic point of view in relation to traditional systems to obtain more expressive results in water quality for reuse, justifying its adoption. The objective of this study was to evaluate an integrated technique for the treatment of urban sewage, by physical-chemical process, followed by separation by membranes. The study was carried out on a laboratory scale with effluent from a sewage treatment plant by stabilization ponds. JarText were performed using inorganic salts, ferric chloride and aluminum sulfate, to determine the best coagulant and its dosage concentration. After the determination and selection of the best condition, floc-sedimentation was performed to feed a pilot submerged membrane separation system, experiments with MF or UF membranes, both at different operating pressures (10 kPa, 40 kPa). The results indicate that flocculation using aluminum sulphate at a dosage of 200 mg / L obtained better performance. UF presented superior efficiency compared to MF in terms of removal, obtaining better global efficiency. The floc-sedimentation integration with UF at 40 kPa promoted TSS, color and turbidity rejections above 95%, culminating in final permeate concentration values of the order of 1 mg / L, 7 Hz and 2 UT, respectively. Reactions between 80% and 90% were achieved for COD, BOD and phosphorus, with final concentrations in the permeate of approximately 30 mg / L, 7 mg / L and 1 mg / L, respectively. It was also obtained, effective retention of microorganisms, so that there was no presence of total and thermotolerant coliforms in the permeate. This quality allows restricted and unrestricted urban reuse in irrigation of green areas, street cleaning, fire protection, washing of clothes and vehicles, discharges of sanitary basins and recreational uses. The flocsedimentation followed by MF reached removal rates close to UF, except for coliforms, being also a viable alternative from the technical-economic point of view, due to the high permeate flux found, superior to UF. Therefore, the combination of floc-sedimentation and membrane separation processes proved to be a beneficial alternative for the production of reuse water from domestic sewage treated by stabilization ponds.